SIFAT FISIK MEKANIK PAPAN DARI LIMBAH KULIT KAYU GALAM - Purwanto, Djoko (Kementerian Perindustrian, 2013)
Galam wood species (Melaleuca leucadendra) using for raw material bulding, charcoral, and energy. Galam bark wood waste has not been used. The purpose of research utilizing of waste Galam bark for board. Galam bark is cut into pieces with a length of 2 cm, 4 cm and 6 cm, then washed with water and dried naturally to moisture content below 7 %. Adhesives used poly vinyl acetate with a variation of 13 %, 16 %, and 19 % by weight of raw material. Cold pressing for 24 hours and a pressure of 15 kg/cm2. Parameters tested water content thickness swelling, density, modulus of elastisitas/MOE, modulus of rupture/MOR, screw withdrawal and tensile strength refers to the test metodhe SNI 03-2105-2006. The test results obtained water content between 13.59 to 15.52 %; thickness swelling between 5.85 to 20.65 %; density of between 0.38 to 0.90 gr/cm3; modulus of rupture / MOR between 8.62 - 56.12 kg/cm2 ; modulus of elasticity / MOE between 311.18 to 4022.33 kg/cm ; tensile strength between 0.16 - 0.55 kg/cm2; screw withdrawal strength between 30-70 kg. Bark size 6 cm long wood with a 19 % concentration of adhesive produced water content, thickness swelling, density, modulus of rupture / MOR, modulus of elasticity / MOE, screw withdrawal strength and tensile strength of the best.Keywords: galam, bark wood, board, physical mechanical.